Fundamentals of medical biotechnology - Prajapat, Rajneesh (Recent trends in biotechnology, 2021)
"Biotechnology, an allied subject of biology, is also associated with its neighboring subject areas, such as: biochemistry, biophysics, biostatistics, pharmacology, cell biology, molecular biology, clinical biology, genomics and proteomics and nanotechnology, which makes this subject an advanced area in medical and health sciences. The exponential growth of the above fields in the past three decades, particularly information technology and biomedical technology and their myriad applications in medicine and health sciences, makes the field of biotechnology a potential front runner. The sophistication in biological techniques and methods makes biotechnological studies more precise, interesting, measurable and reproducible. Fundamentals of Medical Biotechnology is designed to cover all the areas of biotechnological advancement in cell biology, genetics, molecular biology, biochemistry, metabolism, microbiology, clinical pharmacology, immunology, biostatistics and bioinformatics. It helps students of biology, biotechnology, medical sciences and other health sciences to learn the advancement in the field of biomedicine and biotechnology. The book also covers the basics of diagnostic techniques in clinical biochemistry, specific to the technologies addressed in various chapters in the book, at both theoretical and application levels. The book focuses on why these techniques are useful in a clinical context and considers their potential uses, limitations and the ethical considerations that surround their use. This book is based on the recent development in the research dynamics of medical biotechnology, biochemistry and the progress in these fields. It also provides current reference material for students entering the field of medical and bioinformatics, academicians as well as research scientists. The book is a useful source of knowledge for students at senior secondary level, undergraduate and postgraduates in biotechnology and allied subjects, and MBBS / BDS level students looking for an accessible introduction of the subject"--